Evidence from U–Pb zircon geochronology for early Neoproterozoic (Tonian) reworking of an Archaean inlier in northeastern Shetland, Scottish Caledonides - Jahn, I.; Strachan, R.; Fowler, M.; Bruand, E.; Kinny, Peter; Clark, Christopher; Taylor, R. (Geological Society Publishing House, 2017)
Meta-igneous lithologies of the Cullivoe inlier in NE Yell, Shetland, have tonalite–trondhjemite–granodiorite (TTG) chemistry and yield U–Pb zircon crystallization ages of c. 2856 – 2699 Ma. Formation was coeval with protoliths of the Lewisian Gneiss Complex and the time of major Neoarchaean crustal growth in the North Atlantic Craton. The adjacent metasedimentary Yell Sound Group accumulated between c. 1019 and c. 941 Ma. The Cullivoe inlier and the Yell Sound Group were metamorphosed at c. 944 – 931 Ma, the former preserving granulite-facies mineral assemblages inferred to be of this age. Similar-aged metamorphic events recorded in other Laurentian metasedimentary successions in the North Atlantic region are attributed to development of the Valhalla orogen along the Rodinia margin. Ordovician (482 ± 30 Ma) and Silurian (428 ± 16 Ma) thermal rejuvenation resulted from successive phases of the Caledonian orogeny during closure of the Iapetus Ocean. The mechanism by which the Cullivoe inlier was emplaced into its current structural setting is uncertain. Either its western or eastern boundary is a major tectonic break, probably an early ductile thrust. However, this is now cryptic as a result of the Caledonian ductile reworking. © 2017 The Author(s).